Die voorspelling van kredietrisiko met behulp van biografiese veranderlikes: Is dit die antwoord? - P. L.S. Ackermann; W. P. Jansen van Rensburg (South African Journal of Business Management, 1983)
– The prediction of credit risk by means of biographic variables: Is this the answer? The objective of this study is to identify specific biographical variables, to quantity them and to investigate their relative importance in the prediction of credit risk. A representative sample of 250 bad credit risk clients and 250 good credit risk clients is used in the study. A multiple stepwise regression analysis and multiple stepwise discriminant analysis were carried out. Nine biographical variables were identified which explain approximately 16% of the variance of credit risk.
Keywords: 650